CHARACTERISTICS OF CHILDREN IN ISLAMIC EDUCATION IN THE FAMILY IN THE PANDEMIC TIME - Ilmas Uzza Abdul Aziz; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
Character education is a process of applying moral and religious values to students through science, the application of these values to oneself, family, fellow friends, education and the surrounding environment as well as God Almighty. The social development of elementary school age children has increased, initially only socializing with family at home, then gradually getting to know the people around them. Children at this age are also familiar with the digital lifestyle during the pandemic, be it from home, friends, school and the surrounding environment. The digital era in the pandemic era is not only a positive impact, but also a negative impact, hereinafter our role as parents, education and adult society, guiding and supervising children to live it well, accurately, and positively beneficial for the children themselves.Keywords: Character Education, Elementary School Children, During the Pandemic